2012
DOI: 10.1097/bcr.0b013e318254d2ec
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Epidermal Necrolysis

Abstract: Toxic epidermal necrolysis (TEN) represents the most severe drug-related skin condition that is potentially life-threatening with no well-established treatments. The application of corticosteroid therapy is controversial, whereas recently intravenous immunoglobulin (IVIG) therapy is emerging as a promising new method. A severity-of-illness score for TEN (SCORTEN) has gained acceptance in some western countries. In this study, our objectives were to assess the applicability of SCORTEN in Chinese patients with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Of these, 3 studies recruited patients with SJS only[9, 36, 37], 5 studies chose TEN patients only[26, 31, 38–40] and 7 studies imposed no restrictions about patients recruitment[25, 27, 32, 41–44]. There were 628 individuals included in the analysis, which contained 317 controls applied with steroid only and 311 cases treated by combination of IVIG and corticosteroid.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 3 studies recruited patients with SJS only[9, 36, 37], 5 studies chose TEN patients only[26, 31, 38–40] and 7 studies imposed no restrictions about patients recruitment[25, 27, 32, 41–44]. There were 628 individuals included in the analysis, which contained 317 controls applied with steroid only and 311 cases treated by combination of IVIG and corticosteroid.…”
Section: Resultsmentioning
confidence: 99%
“…Ages varied with a range from below 1 to above 90. Most of these studies used median and range to describe them, however, a few articles[25, 40, 44] reported ages using mean and SD. With regards to sex ratio, it seemed to have a female predominance among SJS/TEN patients.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations